Substituted phenylhydrazones of thio-phene-2-carboxaldehyde - Öcal, N; Kaban, S (NATL INST SCIENCE COMMUNICATION, 1998)
Some new phenylhydrazones of thiophene-2-carboxaldehyde have been obtained in 54-96% yield from the condensation of thiophene-2-carboxaldehyde with nitro-substituted-phenyl-N-methylhydrazines, 4-bromo (and chloro)-2-nitrophenyl-N-methylhydrazines and 5-bromo (and chloro)-2-nitrophenylhydrazines.
Keywords: Chemistry